Yield attributes, yield and economics of wheat (Triticum aestivum) + compact mustard (Brassica juncea) intercropping under 5:1 row proportion in relation to fertility levels and seeding densities of two wheat varieties - Singh, Amit Kumar; Bohra, J S (The Indian Journal of Agricultural Sciences, 2012)
A two-year field experiment was conducted during rabi season of 2005–06 and 2006–07 at Varanasi on wheat + compact-mustard intercropping in 5:1 row proportion. The treatments involved three fertilizer doses, i e 100%, 120% and 140% of recommended NPK to wheat accompanied with 100% recommended NPK to mustard; two wheat varieties (HD 2824 and HUW 468) and three seed rates of wheat (100 kg, 115 kg and 130 kg/ha). Increasing fertilizer doses from 100% to 140% RFD applied to wheat accompanied with 100% RFD to mustard exhibited marked increase in yield-attributing characters, grain yield and straw yield. Application of 120 and 140% RFD recorded 6.4 and 10.2% higher LER respectively than 100% RFD. Similar trend was observed for RCC, AYL, IA, net returns and monetary advantage. Conversely, all the fertility levels didn't cause any significant variation on yield attributes, yield, LER, AYL and monetary returns of intercrop mustard. The wheat variety HIV 2824 showed distinct superiority over HUW 468 with respect to spikes/m, test weight, grain yield/m, grain yield, straw yield, LER, RCC, net returns and monetary advantage in wheat + mustard intercropping system. Increasing wheat seed rates from 100 to 130 kg/ha reduced the average spike length, test weight and harvest index though the differences being significant only between lowest and highest seed rates. However, increasing wheat seed rates up to highest level resulted in lucid improvement of spikes/m, grain yield/m, grain yield, LER, RCC, net returns and monetary advantage. However, the reverse trend was noticed for AYL and 1A.